2015
DOI: 10.1080/10408398.2013.781012
|View full text |Cite
|
Sign up to set email alerts
|

Whole grain in manufactured foods: Current use, challenges and the way forward

Abstract: Some countries now incorporate recommendations for increased consumption of whole grain (WG) into local dietary guidelines. Cereal and pseudo-cereal grains are good sources of complex carbohydrates, dietary fiber, proteins, phytochemicals, vitamins and minerals. However, research shows that the large majority of consumers are still falling short of WG consumption goals. To address this, we are actively involved in research to help increase the WG content of processed foods without compromising on taste and tex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 63 publications
0
41
0
Order By: Relevance
“…Low GI diets have been shown to improve glucose and lipid levels and weight control because they help control appetite [30,31]. Low GI diets also reduce insulin resistance and the risk of cardiovascular diseases, diabetes and some cancers [9,24,32]. It is reported that fasting insulin is lower in individuals with higher dietary fiber intakes [33] and that the ingestion of complex carbohydrates promotes longevity [14]; and also that a high GI diet increases the levels of inflammation biomarkers.…”
Section: Glycemic Index (Gi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Low GI diets have been shown to improve glucose and lipid levels and weight control because they help control appetite [30,31]. Low GI diets also reduce insulin resistance and the risk of cardiovascular diseases, diabetes and some cancers [9,24,32]. It is reported that fasting insulin is lower in individuals with higher dietary fiber intakes [33] and that the ingestion of complex carbohydrates promotes longevity [14]; and also that a high GI diet increases the levels of inflammation biomarkers.…”
Section: Glycemic Index (Gi)mentioning
confidence: 99%
“…Traditional food patterns rich in complex carbohydrates, micronutrients, fiber and phytochemicals are being replaced with diets high in animal fats and refined carbohydrates and oils, a situation that has made a direct impact on the prevalence of certain chronic diseases [9]. For this reason, many researchers devote their efforts to analyzing food or food components that may prove to be healthy for human consumption [5]; one example is the work of the HEALTHGRAIN Consortium, which, of note, has included quinoa in its list of healthy grains [10].…”
Section: Nutritional Profilementioning
confidence: 99%
“…Country-wise differences in perception of health-related messages in cereal based food products were demonstrated in Saba et al (2010) and Shepherd et al (2012). Schaffer-Lequart et al (2015) reviewed the current use and challenges of wholegrain in manufactured foods, as well as possibilities to increase the intake. However, their paper did not discuss sensory characteristics of wholegrain products.…”
Section: Consumer Perception Of Wholesome Cereal Productsmentioning
confidence: 99%
“…The ultimate goal of a shared definition is to increase consumption of WG foods and make them more available throughout the food environment. Industry can play a key role in facilitating this and in helping consumers include WGs as a regular part of their diet (36). Although the food industry has come under public scrutiny about the effect of processed foods on human health, food technologists are actively involved in research to develop innovative approaches to increase the range of WG products without compromising on health, taste, and texture (36,37).…”
Section: Resultsmentioning
confidence: 99%
“…Industry can play a key role in facilitating this and in helping consumers include WGs as a regular part of their diet (36). Although the food industry has come under public scrutiny about the effect of processed foods on human health, food technologists are actively involved in research to develop innovative approaches to increase the range of WG products without compromising on health, taste, and texture (36,37). As the food industry continues to introduce new varieties of WG products into the market, consumers need to receive clear and consistent messaging around WGs.…”
Section: Resultsmentioning
confidence: 99%